Azevém anual submetido à doses de nitrogênio, fósforo e potássio em solos de várzea da fronteira oeste do RS - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The experiment conducted in June and October 2014, in the Federal University of Pampa (UNIPAMPA, Itaqui–RS), aimed to evaluate the total herbage mass (DM kg/ha) and the morphogenesis of tillers (m²) of Annual Ryegrass (Lolium multiflorumL.) tetraploid cultivar Barjumbo in typical soil of the western border of Rio Grande do Sul, which are characterized by water-logging and shallow. For this purpose, it was established in randomized block design, managed in a controlled environment with a 4x2 arrangement, with four replicates and submitted to different levels of fertilization, with four levels of N (0,75, 125 and 175%) and two levels of P and K(100 and 150) % of the recommended dose. It was evaluated the total production of dry matter (DM kg/ha) and tiller density (m²). The characterization of Annual Ryegrass pasture for levels of P and K, showed no interactions between the variables evaluated. Nitrogen fertilization influenced on the production of dry matter and tiller density. However, tiller density did not change as a function of P and K (p>0.05). It can be said that the higher productivity due to an increase of nitrogen for DM production (P and K 100%) reached a maximum value of 116.31% and in treatments with 150% P and K, the maximum point was120.70 % of the recommendation. Similarly for tiller density/m² (100% P and K), the point was 75.38% and for 150% P and K the point was 78.24% of the recommended dose. Therefore, the use of larger doses of N (%) coincides with low productivity, whereas higher doses than those estimated, there is a decrease in productivity in the production of both dry matter and in the number of tillers.
Keywords: Nutrição mineral; Perfilhamento; Produção de matéria seca; Dry matter production; Mineral nutrition; Tillering; Lolium multiflorum L.; CNPQ::CIENCIAS EXATAS E DA TERRA